2019
DOI: 10.3168/jds.2018-15418
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of normal and atypical progesterone profiles in Holstein-Friesian dairy cows

Abstract: Female fertility has a major role in dairy production and affects the profitability of dairy cattle. The genetic progress obtained by traditional selection can be slow because of the low heritability of classical fertility traits. Endocrine fertility traits based on progesterone concentration in milk have higher heritability and more directly reflect the cow's own reproductive physiology. The aim of our study was to identify genomic regions for 7 endocrine fertility traits in dairy cows by performing a genome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…The low heritability estimates for the classical fertility traits could be attributed to a multitude of factors, including, for example, that the traits are truly under poor additive genetic control relative to nonadditive and nongenetic factors (Berry et al, 2012). It is also claimed that low heritability estimates together with an unfavorable relationship between production and fertility traits complicates genetic improvement (Nyman et al, 2019). Daetwyler et al (2008) pointed out that the level of heritability for a trait influences the success of genome-wide association studies.…”
Section: Estimates Of Heritability and Genetic Correlationmentioning
confidence: 99%
“…The low heritability estimates for the classical fertility traits could be attributed to a multitude of factors, including, for example, that the traits are truly under poor additive genetic control relative to nonadditive and nongenetic factors (Berry et al, 2012). It is also claimed that low heritability estimates together with an unfavorable relationship between production and fertility traits complicates genetic improvement (Nyman et al, 2019). Daetwyler et al (2008) pointed out that the level of heritability for a trait influences the success of genome-wide association studies.…”
Section: Estimates Of Heritability and Genetic Correlationmentioning
confidence: 99%
“…JARID2 is a gene located within the QTL which is associated with the development of the hind quarter [112], and it is located in the window from the GWAS explaining >1% of the genetic variation of the performance traits of angus cattle in high-altitude regions (elevation at 2170 m) [113]. Nyman et al [114] point to JARID2 as a possible candidate gene for cow fertility traits.…”
Section: Candidate Genes and Genomic Regions Identified By Gwasmentioning
confidence: 99%
“…In this study, we focused on a specific type of fertility traits, the endocrine traits. Quantitative trait loci studies regarding endocrine traits are much less common, and only a few studies have reported QTL (Berry et al, 2012;Tenghe et al, 2016;Nyman et al, 2019).…”
Section: Qtl Overlapping Between Studiesmentioning
confidence: 99%